Validation of RUMINANT model of enteric methane emissions - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The RUMINANT model was validated for enteric methane emissions from cattle in the tropical lowlands (Cauca Valley) of Colombia. Based on findings from the validation process, RUMINANT is available as a tool for providing rigorous information on animal productivity and mitigation potential at relatively low cost in Colombia.